Develop the Precise Vacuum Seeder for Nursery Plug Tray Sowing by Using the Vacuum Cleaner - Yenphayab Charatchai; Saijai Jedsada; Hongwiangjan Jeerayut (BIO Web of Conferences)
The manual sowing of vegetable seeds is the general practice of vegetable nurseries in Thailand. It is the slow and labour-intensive process that causes the low production capacity. This study aims to design and develop a vegetable seed sowing machine for 200-cell plug tray plantings to substitute human labor. The prototype utilizes the vacuum cleaner to develop the suction head pressure that simultaneously offers the 200 seeds-planting per tray. The vacuum seeder mechanism is composed of the suction head unit and seeds tray unit. The prototype is operated and controlled by the automation system for continuous planting. Cantonese vegetable seed is selected to evaluate the planting precision of the prototype. Based on the design parameters obtained in laboratory experiments, the optimal condition for planting the Cantonese vegetable seeds in the 200-cell plug tray is verified by adjusting two parameters the suction pressures and the nozzle implement type. On the other hand, the planting precision is indicated by the single seed sowing index. The results showed that the average quality of feed index is 70.53% when utilizing the large nozzle implement type with a vacuum pressure of 1019 Pa. The average working cycle time per tray and the machine capacity per hour are 51.0 seconds and 70 trays, respectively. Moreover, the prototype machine costs about 43% of the average cost of the existing commercial seeders in terms of cost-effectiveness.